Kolonialisme, Kerbau, dan Sarekat Islam: Ekspresi Kekhawatiran Potensi Gerakan Sarekat Islam terhadap Kekuasaan Belanda - Faizal Arifin (Universitas Hamzanwadi, 2025)
This study analyzes the symbolism of the buffalo in the colonial caricature De Inlandsche Karbouw, which portrays the resistance of Sarekat Islam against Dutch rule, contextualized with various primary sources. Initially established as a Muslim organization with an economic focus, Sarekat Islam evolved into a socio-political movement advocating justice for the indigenous population, causing alarm among the Dutch both in the colony and in the Netherlands. This research employs historical methods, including heuristics, source criticism, interpretation, and historiography. The results indicate that the Dutch colonial government perceived this movement as a significant threat, as reflected in the De Inlandsche Karbouw caricature, which served as propaganda attempting to depict Sarekat Islam as a formidable force yet ostensibly controllable by the colonial administration. However, this supposed control was, in reality, illusory, as historical analysis demonstrates that Sarekat Islam grew massively and remained unstoppable. The symbolism of the giant buffalo illustrates the relentless expansion of Sarekat Islam’s influence, rendering the efforts of Pleyte, Boogaardt, Schuerer, Vliegen, and van Deventer ineffective, much to the delight of Douwes Dekker. This study highlights how Dutch colonialism used visual representation to shape public opinion and suppress the independence movement in Indonesia.